Advancement of dental anomalies among children of the Ivano-Frankiv region - Заяць, Олександра Романівна; Ожоган, Зіновій Романович (Actual Dentistry, 2020)
Aim. To study the advancement and features of dental anomalies clinic among children of different age groups to improve the effectiveness of orthodontic treatment. Materials and methods. With the aim of studing the prevalence of dental anomalies, we examined 600 children of the Ivano-Frankivsk region, divided into the following age groups: - 205 children, 3–5 years old (temporary dentition); - 200 children aged 6–9 years (early variable dentition); - 195 children aged 10–12 years (late variable dentition). The examination were conducted in organized groups of children (kindergarten, school). The obtained informationwas entered into a specially designed for each child «Card of epidemiological examination of children», which shows zthe passport data of the child, dental formula, bite period, index kp (caries-seal), kp + KPV (caries-seal-removed), the number of prematurely removed teeth, the presence of bad habits, the type of dental anomaly, the presence or absence of orthodontic treatment. Results. According to the results of researches, the growth of advancement of carious process with the age is revealed, and these factors leads to gradual destruction and subsequent loss of milk teeth and creation of favorable conditions for the development of deformations of dental rows. It was found that at the age of 3 years the prevalence of distal and open bites was significantly higher due to the presence of bad habits, especially sucking and biting of objects, and at the age of 4–5 years there was a redistribution towards mesial, deep and cross bites, which could be associated with high prevalence of carious process, loss of crown parts of teeth, premature removal of milk teeth. At the age of 6–9 years, high prevalence of anomalies of the position of individual teeth, anomalies of the form of dentition and distal occlusion were found, and among children of 10–12 years the highest incidence of anomalies of the position of individual teeth, anomalies of the form of dentition and distal occlusion. Therefore, it is of great importance to carry out routine preventive examinations of children in schools and preschool institutions for the possibility of timely restoration of the integrity of the crowns of baby teeth, preventive prosthetics of children with defects of the dental rows, the elimination of bad habits and effective influence on the formation of the dentition system by means of orthodontic measures. Conclusions. 1. The high advancement and intensity of the carious process leads to premature removal of the milk teeth and creates favorable conditions for the development of dental anomalies and deformities. 2. In 90.9 % of cases of premature removal of baby teeth, especially in the lateral area, there is a pathological mesial displacement of the permanent teeth, which is one of the main causes of dental anomalies. 3. Considering the results of the research, it is necessary to emphasize the need for routine preventive examinations of children in schools and preschool institutions for the possibility of timely restoration of the integrity of the crowns of milk teeth, prophylactic prosthetics of children with defects of the dental rows, elimination of bad habits and effective influence on the formation of the dental system. activities. Key words: caries prevalence, dental malformations, premature removal of temporary teeth, epidemiological studies.